2004
DOI: 10.1249/01.mss.0000145447.61736.ed
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Changes in tPA and PAI-1 after Maximal Exercise

Abstract: To accurately evaluate the t-PA response to acute exercise, blood samples should be collected within 2 min after the cessation of exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…Although behavioral or environmental factors such as activity level could also influence PAI-1, our 15-minute mild stress tests likely did not capture the full range of PAI-1 changes that can be induced by behavior. 14,15 This complexity is highlighted by a study that found a blunted PAI-1 rhythm in 2 blind individuals who were not synchronized to the 24-hour light/dark cycle. 16 In animals, lesioning the central circadian pacemaker (suprachiasmatic nucleus) abolished the daily rhythm in PAI-1 17 but also abolished behavioral rhythmicity so it could not be determined if the PAI-1 rhythm is driven directly by the circadian system or indirectly through behavior.…”
Section: Resultsmentioning
confidence: 99%
“…Although behavioral or environmental factors such as activity level could also influence PAI-1, our 15-minute mild stress tests likely did not capture the full range of PAI-1 changes that can be induced by behavior. 14,15 This complexity is highlighted by a study that found a blunted PAI-1 rhythm in 2 blind individuals who were not synchronized to the 24-hour light/dark cycle. 16 In animals, lesioning the central circadian pacemaker (suprachiasmatic nucleus) abolished the daily rhythm in PAI-1 17 but also abolished behavioral rhythmicity so it could not be determined if the PAI-1 rhythm is driven directly by the circadian system or indirectly through behavior.…”
Section: Resultsmentioning
confidence: 99%
“…The capacity to thrombolize fibrin clots is influenced by many factors of the fibrinolytic system, but particularly tPA and PAI-1. The increased fibrinolytic potential occurs due to an increase of tPA activity or antigen, which catalizes the conversion of plasminogen into plasmin, and/or a decrease in PAI-1 (Collen et al, 1980;Molz et al, 1993;Rankinen et al, 1995;Weiss et al, 1998;El-Sayed et al, 2000;Huber, 2001;Ivey et al, 2003;Cooper et al, 2004;Womack et al, 2006). Under basal conditions, tPA circulates mainly as a complex with PAI-1 with low levels of free tPA, and PAI-1 inhibits tPA by binding to it and forming an inactive complex.…”
Section: Discussionmentioning
confidence: 99%
“…38 Similar data were reported by Lin et al, who observed a significant increase in t-PA and a significant decrease in PAI-1 values after a standardized cycle ergometer test in active young men, which was followed by a sharp fall 2 hours thereafter. 54 However, increases of t-PA (þ361%) and of PAI-1 (þ235%) were observed by Prisco et al 64 in well-trained, long-distance male runners immediately after a marathon run and by Cooper et al 65 in healthy males after a graded maximal exercise test on a treadmill. Significant increases in fibrinopeptide A (FPA) levels, up to 900% of the pre-exercise values, were observed by Röcker et al after a marathon race, reaching peak values 60 minutes after the run.…”
Section: Influence Of Physical Exercise On Secondary Hemostasismentioning
confidence: 94%